New Psychoactive Substances and evolving criminal dynamics against the backdrop of the fourth industrial revolution - Zaami, Simona (Acta Biomedica Atenei Parmensis, 2022)
Invited commentary on Letter: Napoletano S, Basile G, Lo Faro AF, Negro F. New Psychoactive Substances and receding COVID-19 pandemic: really going back to “normal”?. Acta Biomed 2022; Vol. 93, N. 2: e2022186 DOI 10.23750/abm.v93i2.13008 https://www.mattioli1885journals.com/index.php/actabiomedica/article/view/13008